EVALUATION OF LONG-TERM RESULTS OF VIDEOLAPAROSCOPIC RADICAL HYSTERECTOMY WITH APPENDICES AND BILATERAL FIXATION OF THE VAGINAL STUMP IN WOMEN WITH GENITAL PROLAPSE - Dudchenko, V.M.; Hromova, A.M. (World of Medicine and Biology, 2024)
Genital prolapse is a common disease with a severe course. Treatment methods are usually surgical, but the benefits of individual surgical treatments are still an open question. The purpose of the study was to analyze the results of the treatment of women with genital prolapse after 6 and 12 months who underwent videolaparoscopic radical hysterectomy with appendages and bilateral fixation of the vaginal stump. After the above-mentioned surgical treatment of women with genital prolapse, a significant decrease of 5 times was found in the number of women complaining of difficulty urinating, complaints of the feeling of a foreign body in the vagina were noted 3 times less often. Urinary incontinence was not detected in the examined women, as well as a non-specific inflammatory process in the vagina after surgical treatment was noted 9 times less often compared to the same data before the operation.
Keywords: gynecology; surgery; combined operations; laparoscopic operation; operative treatment